Multi-mode navigation autonomous mobile robot - Shahrul Bhari, Mustafa (Universiti Malaysia Perlis, 2008)
The earth is orbited by at least 24 Medium Earth Orbit satellites, and at any instant, one location on earth will be covered between 6-12 satellites. GPS is the protocol system to determine a specific location on earth by triangulation of microwave signals. A typical GPS receiver calculates its position using the signals from four or more GPS satellites. Four satellites are needed since the process needs a very accurate local time, more accurate than any normal clock can provide, so the receiver internally solves for time as well as position. In other words, the receiver uses four measurements to solve for 4 variables - x, y, z, and t. These values are then turned into more user-friendly forms, such as latitude/longitude or location on a map, and then displayed to the user. The information may be used to determine to location of any systems that is allowed to roam any areas to provide information of its location. The research implements GPS for autonomous robot navigation for outdoor applications. The GPS module is interfaced to the microcontroller as the system needs to read or write the information of location of autonomous robot. The Basic Stamp 2 is one of microcontroller that can communicate with the GPS module. It is proved that the GPS is most reliable system in navigation for many applications, from this project it is prove the statement.